Children’s contact with nature in low-income neighborhoods: parents’ and teachers’ perspectives - Moore, Emily (Kansas State University, 2024)
A growing body of literature reveals children are spending less time in nature in recent years (Clements, 2004; Luís et al., 2020). Both perceived and physical accessibility to greenspaces can contribute to children’s positive usage of these spaces, especially for disadvantaged communities including, low-income and/or racially minoritized populations (Bates et al., 2018; Strife & Downey, 2009). This study aims to explore how elementary school teachers’ and parents’ perceptions and attitudes of children’s contact with nature can inform recommendations to improve children’s access to and contact with nature. With its history of redlining and current social and spatial inequalities, Kansas City, Missouri serves as a suitable case to assess greenspace equity for children in low-income communities (González-Pérez, 2021). The study was conducted in one elementary school in the Kansas City Public Schools district and uses a mixed methods approach. A socio-demographic analysis was used to select schools in low-income areas with a higher proportion of children aged five to nine years old compared to the rest of the city. Then, spatial analysis of the greenspaces in the participating school’s attendance zone identified the types of greenspaces available to these neighborhoods and nearby the school. Parents (n=31) and teachers (n=20) were surveyed using multi-lingual photo-surveys to gather their perceptions of their children’s access to and contact with nature. Survey responses were entered in the IBM Statistical Package for the Social Sciences (SPSS) 29 software. Analyses included frequencies, correlations, factor and reliability analysis, and independent sample t-tests to understand the strength of and associations between different factors. Findings from the greenspace availability analysis and social statistical analysis revealed that children’s contact with nature was limited, including the types of greenspaces children go to and the exposure of nature during school. However, parents and teachers were aware and had positive attitudes towards the importance of children’s contact with nature, and liked all outdoor settings and activities proposed in the survey. Potential factors that may be associated with children’s contact with nature included their reliance on parent supervision at greenspaces, curriculum, walkability (i.e., unsafe street crossings and sidewalks) and safety concerns (i.e., gunshots, drugs/alcohol, poor maintenance). These findings informed design strategies including re-envision existing greenspaces, create safe and green routes to school and greenspaces, transform vacant lots, and create policy to support planning for children’s contact with nature in the city. Despite the small sample size, this study contributes to the growing body of literature on greenspace accessibility and contact with nature for children. Additionally, it sheds light on potential future research on what factors may be associated with children’s contact with nature using both spatial and social analyses.
Keywords: Contact with nature; Greenspace; Perceptions; Attitudes; Accessibility; Equity